2018
DOI: 10.1001/jama.2017.21896
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Fetal Alcohol Spectrum Disorders in 4 US Communities

Abstract: Estimated prevalence of fetal alcohol spectrum disorders among first-graders in 4 US communities ranged from 1.1% to 5.0% using a conservative approach. These findings may represent more accurate US prevalence estimates than previous studies but may not be generalizable to all communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
274
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 602 publications
(301 citation statements)
references
References 27 publications
1
274
1
3
Order By: Relevance
“…Alcohol, tobacco, and illicit drugs are preferably avoided since maternal use is associated with increased risk of pregnancy complications and poor infant outcomes . Recent findings have demonstrated the underestimation of the prevalence of fetal alcohol spectrum disorders, as well as the negative effects of even low alcohol intake during pregnancy on the craniofacial development of newborns . With regard to preconception intake of folic acid, previous studies have shown that prevalence estimates might differ between different pregnant populations …”
Section: Introductionmentioning
confidence: 99%
“…Alcohol, tobacco, and illicit drugs are preferably avoided since maternal use is associated with increased risk of pregnancy complications and poor infant outcomes . Recent findings have demonstrated the underestimation of the prevalence of fetal alcohol spectrum disorders, as well as the negative effects of even low alcohol intake during pregnancy on the craniofacial development of newborns . With regard to preconception intake of folic acid, previous studies have shown that prevalence estimates might differ between different pregnant populations …”
Section: Introductionmentioning
confidence: 99%
“…A very recent prevalence study in the general US population provided a conservative estimate of 11.3–50 per 1000 children . The prevalence rate of FASD amongst the general population in Australia is currently unknown.…”
Section: Prevalencementioning
confidence: 99%
“…Fetal alcohol spectrum disorders (FASD) encompass the range of physical, cognitive, and behavioral deficits due to prenatal alcohol exposure. Recent estimates suggest a prevalence of ~2–5% among school-age children (May et al, 2014; May et al, 2015; May et al, 2018), identifying FASD as a serious public health concern.…”
Section: Introductionmentioning
confidence: 99%